(untitled) (Clinics, 2013)
OBJECTIVE: Obstructive sleep apnea is common among patients with hypertrophic cardiomyopathy and may contribute to poor cardiovascular outcomes. However, obstructive sleep apnea is largely unrecognized in this population. We sought to identify the clinical predictors of obstructive sleep apnea among patients with hypertrophic cardiomyopathy. METHODS: Consecutive patients with hypertrophic cardiomyopathy were recruited from a tertiary University Hospital and were evaluated using validated sleep questionnaires (Berlin and Epworth) and overnight portable monitoring. Ninety patients (males, 51%; age, 46±15 years; body mass index, 26.6±4.9 kg/m2) were included, and obstructive sleep apnea (respiratory disturbance index ≥15 events/h) was present in 37 patients (41%). RESULTS: Compared with the patients without obstructive sleep apnea, patients with obstructive sleep apnea were older and had higher body mass index, larger waist circumference, larger neck circumference, and higher prevalence of atrial fibrillation. Excessive daytime sleepiness (Epworth scale) was low and similar in the patients with and without obstructive sleep apnea, respectively. The only predictors of obstructive sleep apnea (using a logistic regression analysis) were age ≥45 years (odds ratio [OR], 4.46; 95% confidence interval [CI 95%], 1.47-13.54; p = 0.008) and the presence of atrial fibrillation [OR, 5.37; CI 95%, 1.43-20.12; p = 0.013]. CONCLUSION: Consistent clinical predictors of obstructive sleep apnea are lacking for patients with hypertrophic cardiomyopathy, which suggests that objective sleep evaluations should be considered in this population, particularly among elderly patients with atrial fibrillation.